Discrimination of common Iris species from Egypt based on their genetic and metabolic profiling. Issue 2 (26th April 2020) - Okba, Mona M.; Abdel Baki, Passent M.; Khaleel, Amal E.; El‐Sherei, Moshera M.; Salem, Mohamed A.
Abstract: Introduction: Irises have been medicinally used in Ancient Egyptians, Anatolian, Chinese, British and Irish folk medicine. They are also well‐known ornamental plants that have economic value in the perfume industry. The main obvious diagnostic difference between the different species is based on the morphology of the flowers. The flowering cycle is very short as well as the persistence of the fully opened flowers extends for a few days only. Moreover, the climatic conditions significantly causes fluctuation in their blooming time from year to year. This makes the morphological discrimination very difficult. The discrimination of different iris species is of a great importance, as each species is reported to possess different folk medicinal activities. Objectives: Finding genetic and metabolic markers for differentiation between Iris confusa Sealy (Subgen. Limniris Sect. Lophiris ), I. pseudacorus L. (Subgen. Limniris Sect. Limniris ) and I. germanica L. (Subgen. Iris Sect. Iris ) on levels other than traditional taxonomic features. Material and Methods: Inter‐simple sequence repeat (ISSR) and gas chromatography–mass spectrometry (GC–MS) analyses were performed. Results: The highest similarity was found between I. pseudacorus L. and I. germanica L. and the least similarity was between I. confusa Sealy and I. pseudacorus L. The metabolic profiling of the leaves confirmed genetic profiling discriminating I. confusa from the other two species. The primary metabolites of the underground parts showed clear discrimination between the three species. Conclusions: This study represents the sole complete map for distinguishing the three Iris species on genetic and metabolic bases. Abstract : Inter‐simple sequence repeat and gas chromatography–mass spectrometry (GC–MS) analyses were performed with the aim of finding genetic and metabolic markers for the differentiation between the three Irises ( Iris confusa Sealy, I. pseudacorus L. and I. germanica L.) on levels other than their taxonomic characters. The metabolic profiling of the leaves confirmed genetic profiling discriminating I. confusa from the other two species while that of the underground parts showed clear differentiation among the three species.